1995
DOI: 10.1152/ajpendo.1995.269.3.e499
|View full text |Cite
|
Sign up to set email alerts
|

Response of leucine metabolism to hyperinsulinemia under amino acid replacement in experimental hyperthyroidism

Abstract: We investigated the responsiveness of protein metabolism to insulin as a mediator of the protein catabolic response to hyperthyroidism in humans. Six healthy volunteers were studied in a postabsorptive state before and after oral intake of thyroid hormones (2 micrograms.kg-1.day-1 L-thyroxine for 6 wk along with 1 microgram.kg-1.day-1 triiodothyronine for the last 2 wk). Insulin was infused at 7.14 nmol.kg-1.min-1 for 140 min under euglycemic and eukalemic clamps. An appropriate amino acid infusion was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 16 publications
6
21
0
1
Order By: Relevance
“…This is in keeping with the notion that thyroid hormones have both anabolic and catabolic actions, as suggested by the reports of Rochon et al (29) and Tauveron et al (35) using a leucine tracer method. At the whole body level, we observed a 40% increase in protein synthesis rate (calculated as total phenylalanine flux Ϫ phenylalanine-to-tyrosine degrada- Data are presented as means Ϯ SE.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in keeping with the notion that thyroid hormones have both anabolic and catabolic actions, as suggested by the reports of Rochon et al (29) and Tauveron et al (35) using a leucine tracer method. At the whole body level, we observed a 40% increase in protein synthesis rate (calculated as total phenylalanine flux Ϫ phenylalanine-to-tyrosine degrada- Data are presented as means Ϯ SE.…”
Section: Discussionsupporting
confidence: 88%
“…Studies of protein metabolism in hyperthyroid patients before and after treatment have suggested that the net protein catabolism is mainly because of depressed rates of whole body protein synthesis (7,20) with low or normal rates of proteolysis. In experimental hyperthyroidism, increased rates of proteolysis with no change in protein synthesis rates have been reported (6,16), whereas Tauveron et al (35) found both increased proteolysis and synthesis. Thyroid hormones have both anabolic and catabolic effects; therefore, the net effect on protein metabolism may vary, and the above inconsistencies may relate to heterogeneity both of the hyperthyroid subjects, in terms of severity and duration of hyperthyroidism, and of the methods employed.…”
mentioning
confidence: 95%
“…However, in a previous study, we showed that a similar amino acid-glucose infusion, albeit in the presence of insulin, did not stimulate the nonoxidative leucine disposal in healthy subjects. As was observed in the PIϪ group in the present study, amino acid-glucose infusion also impaired nonoxidative leucine disposal (Ϫ10%) (41). Moreover, Giordano et al (14) clearly showed that amino acid infusion, which increased plasma amino acids by 1.25-1.50 above baseline (as in the present study), did not change nonoxidative leucine disposal in healthy volunteers.…”
Section: Discussionsupporting
confidence: 84%
“…Total whole body leucine turnover rate (Q, mol ⅐ kg Ϫ1 ⅐ min Ϫ1 ) was determined using the equation (28,25,41,43,44)…”
Section: Methodsmentioning
confidence: 99%
“…Similar effects were recorded in normal volunteers and dysthyroid patients when glucose and amino acids were given along with insulin [27,28]. Indeed insulin is known to mediate the decrease in proteolysis.…”
Section: Discussionsupporting
confidence: 68%